Development of active UWB localization systems for fast and micro movement tracking - Chong, Pei Jie. (2012)
The objectives of this project are to develop and analyze an ultra-wideband wireless localization tracking system, using the ultra-wideband (UWB) pulse arrival time measurements. UWB is a break-through application of a radio frequency (RF) technology which can deliver up to 15cm 3D positional accuracy. Its technique application enables an ultra-low power transmission with high precision localization using pulse measurement. UWB is able to detect effectively on highly accurate positions of tags both indoors and outdoors and then record the location data to the database. These include storing location information for path history tracking, triggering events using location information, and location information as an efficient indicator.